Comparisons are Odious? The neural basis of in-group and out-group social comparison among game players: An fMRI study - Fang, Zijie; Wen, Hongwei; Zhou, Yuhong; Gao, Xuemei (Behavioural brain research, 2024)
Social comparison is an important way for individuals to define their social characteristics. Online games with a large amount of social information provide a convenient platform for social comparison between players. However, few studies have examined the neural basis of different social comparisons in game players. This study aims to explore the activation of brain regions triggered by social comparison in different contexts and the possible moderating effect of group identity. A total of 26 subjects participated in our experiment. We referred to the minimum group paradigm to evoke group identity and used the dot estimation paradigm to generate in-group or out-group social comparisons. The activation of brain regions was measured and analyzed. Compared to upward comparison, the fusiform gyrus, putamen, lentiform nucleus, precuneus, and precentral gyrus were significantly activated in downward comparison when the group identity of the comparison object was the same as that of the player. When the two had different identities, downward comparison significantly activated the angular gyrus, middle frontal gyrus, and superior frontal gyrus. However, the moderating effect of group identity was not significant. Further functional connectivity analysis based on the brain region activation results was performed. Our study has shown that social comparison in group contexts leads to the activation of different brain regions and provides neurophysiological evidence of social interaction among game players.